Правосуб’єктність фізичних осіб у сфері правовідносин працевлаштування - Вусенко, Ю.; Vusenko, Y. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Досліджено складники трудової правосуб’єктності фізичних осіб, які шукають роботу у сфері правовідносин працевлаштування. Необхідними елементами набуття трудової дієздатності в цій сфері правовідносин є працездатність та працездатний вік особи, її готовність приступити до роботи. У сучасних умовах ринкових змін коло осіб, які стають суб’єктами правовідносин працевлаштування, розширюється, тому мають бути змінені умови набуття трудової правосуб'єктності відповідно до міжнародно-правових стандартів та норм права України.Components of the labor legal personality of individuals who are looking for a job in the field of legal relations of employment are investigated. Required items of the acquisition the labor legal capacity in these relations are: working capacity and working age of the person, his readiness for work, and the issue of determining the components of labor legal personality of individuals, as one of the most relevant concepts in the theory of labor law to which a large amount of scientific papers of the Soviet and the modern period are devoted. Considering that in current conditions of market changes a circle of individuals who are the subjects of legal relations of employment is expanding, conditions for the acquisition legal personality as the main properties of the subject of legal relations are changing, the conditions of a legal personality in this article are defined.
Legal Personality of Individuals in the Field of Legal Relations of Employment.
Keywords: працевлаштування; безробітні; зайняті та незайняті фізичні особи; трудова правосуб’єктність; employment; unemployed; employed and unemployed individuals; labor legal personality